2012
DOI: 10.1021/np300077r
|View full text |Cite
|
Sign up to set email alerts
|

Antiprotozoal Sesquiterpene Pyridine Alkaloids from Maytenus ilicifolia

Abstract: As part of a bioprospecting program aimed at the discovery of antiprotozoal agents from the Brazilian flora, two new sesquiterpene pyridine alkaloids, ilicifoliunines A (1) and B (2), along with the known alkaloids aquifoliunine E-I (3) and mayteine (4), were isolated from the root bark of Maytenus ilicifolia. The structures of 1 and 2 were established on the basis of spectroscopic data interpretation. Alkaloid 3 displayed potent in vitro antiprotozoal activity against Leishmania chagasi and Trypanosoma cruzi,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…The small coupling constant of J1,2 = 3.6 Hz between H-1 and H-2 indicated that the H-2 was equatorial. These data revealed that the relative configuration of the dihydro-β-agarofuran sesquiterpene core in 1 was identical to that of triptonine A [10] and the related compounds [12,27,28]. The relative configurations of the groups at two macrocyclic rings were determined by comparison of the NMR spectroscopic data with those of triptonine A [10], which was established by X-ray crystallography.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…The small coupling constant of J1,2 = 3.6 Hz between H-1 and H-2 indicated that the H-2 was equatorial. These data revealed that the relative configuration of the dihydro-β-agarofuran sesquiterpene core in 1 was identical to that of triptonine A [10] and the related compounds [12,27,28]. The relative configurations of the groups at two macrocyclic rings were determined by comparison of the NMR spectroscopic data with those of triptonine A [10], which was established by X-ray crystallography.…”
Section: Resultsmentioning
confidence: 85%
“…Its UV spectrum showed absorption bands at λmax 231 and 253 nm, indicating the presence of aromatic rings. In the 1 H-NMR spectroscopic data of 1 (Table 1) [23,[25][26][27][28]. An evoninic acid moiety [25][26][27][28][29] (Table 1) along with DEPT and HSQC spectra showed the presence of the units mentioned above in 1.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Absorbances were read at 490 nm. The drug concentration corresponding to 50% of parasite growth inhibition was expressed as the inhibitory concentration (IC50) in μM [10].…”
Section: Animalsmentioning
confidence: 99%
“…All the assays were performed in triplicate. Test samples concentrations corresponding to 50% of parasite growth inhibition (IC 50 ) were determined from non-linear regression (Muelas-Serrano et al 2000;Santos et al 2012).…”
Section: In Vitro Assay For Trypanocidal Activitymentioning
confidence: 99%